Pigment epithelium-derived factor protects the morphological structure of retinal Müller cells in diabetic rats - Xiao-Hui Zhang (International Journal of Ophthalmology, 2014)
AIM:To investigate if pigment epithelium-derived factor (PEDF) has any protective effect on the retinal Müller cells of Sprague-Dawley rats suffering from diabetes mellitus.METHODS:Sixty Sprague-Dawley rats were randomly divided into a negative control group, a group receiving 0.1 μg/μL PEDF, another group receiving 0.2 μg/μL PEDF, and a group receiving balanced salt solution (BSS). Rats in both the PEDF and BSS groups were treated intravitreally based on previously established diabetic models. After 4wk of treatment, morphological alterations of Müller cells and protein expression of glutamine synthase (GS) and glial fibrillary acidic protein (GFAP) were analyzed.RESULTS:PEDFat either0.1 μg/μL or 0.2 μg/μL significantly improved the structures of both nuclei and organelles of Müller cells compared to the BSS-treated group. Expression of GS was significantly higher in the 0.2 μg/μL PEDF group than that in the BSS group (P=0.012), but expression of GFAP was significantly lower in the 0.2 μg/μL PEDF group than that in the BSS group (P=0.000); however, there were no significant differences in expression of these proteins between the 0.1 μg/μL PEDF group and the BSS group (P=0.608, P=0.152).CONCLUSION:PEDF protects the morphological ultrastructure of Müller cells, improves the expression of glutamate synthase and prevents cell gliosis.